2020
DOI: 10.1108/ijbm-07-2019-0267
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bank branch density: a case study of Slovakia

Abstract: PurposeThis paper studies the density of bank branches in districts of Slovakia and aims to identify determinants that explain or justify districtural differences in the density of bank branches.Design/methodology/approachBank branch density is measured by the number of branches in a district, and banks are further differentiated by size and profile. Potential determinants of bank branch density are sought through univariate and bivariate Poisson regressions amongst economic factors, socioeconomic factors, tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In Slovakia, it was found that the number of branches in the districts is largely determined by factors related to the degree of economic development, the number of inhabitants and the characteristics of the population, as well as the concentration of certain economic branches. Spatial positioning of bank branches is not random but is planned [15]. Site selection is as important for banks as it is for industrial and commercial enterprises and companies [8].…”
Section: Methodsmentioning
confidence: 99%
“…In Slovakia, it was found that the number of branches in the districts is largely determined by factors related to the degree of economic development, the number of inhabitants and the characteristics of the population, as well as the concentration of certain economic branches. Spatial positioning of bank branches is not random but is planned [15]. Site selection is as important for banks as it is for industrial and commercial enterprises and companies [8].…”
Section: Methodsmentioning
confidence: 99%
“…Since a poor site choice would be expensive and difficult to undo, choosing the right location is seen as a crucial decision. Therefore, significant discrepancies in the availability of financial services or abrupt changes or disparities in the operating conditions to which bank branches are exposed serve as the primary drivers of study on the spatial distribution of bank branches [6].…”
Section: Related Workmentioning
confidence: 99%
“…Alamá and Tortosa-Ausina, 2012; Kondo and Harimaya, 2014), and banking competition (e.g. Hannan and Hanweck, 2008; Boďa and Čunderlíková, 2020). Table 1 summarizes the related studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2002). Empirical studies find mixed results concerning the relationship between banking competition and bank branching decisions (Hannan and Hanweck, 2008; Cohen and Mazzeo, 2010; Boďa and Čunderlíková, 2020; Chen and Strathearn, 2020).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%